O004 NIK-IKK complex controls NF-ΚB-dependent inflammatory activation of the endothelium in response to LTΒR ligation. (21st February 2018) - Kucharzewska, P; Jeucken, KCM; Maracle, CX; van Hamburg, JP; Olsson, H; Tas, SW
Abstract : Introduction: Sites of chronic inflammation, such as rheumatoid arthritis (RA) synovial tissue, often contain tertiary lymphoid structures with high endothelial venules (HEV). Ligation of the lymphotoxin (LT)-β receptor (LTβR) results in activation of canonical and NF-κB-Inducing Kinase (NIK)-dependent noncanonical NF-κB signalling in endothelial cells (EC), leading to HEV development. However, the relative contribution of the individual NF-κB pathways to inflammatory activation of EC is largely elusive. Objectives: To identify the molecular pathways by which LTβR drives inflammatory activation of EC to promote interaction with leukocytes. Methods: Primary human EC were treated with LTβ or LIGHT to activate LTβR, followed by analysis of downstream NF-κB signalling pathways and expression of adhesion molecules and inflammatory cytokines. To repress canonical NF-κB signalling pathway, a small molecule inhibitor of IKKβ was used, and noncanonical NF-κB signalling was repressed with siRNAs targeting NFκB2. The role of NIK in LTβR signalling was investigated using small molecule inhibitors and siRNAs targeting NIK, as well as adenoviral overexpression of NIK. The role of NF-κB signalling in RA was measured by stimulating EC with RA synovial fluid (RASF) followed by analysis of inflammatory mediators. Results: LTβR-triggering in EC resulted in activation of both canonical and noncanonical NF-κB signalling, and induced inflammatory cytokine expression and immune cell adhesion. IKKβ inhibition repressed LTβR-induced inflammatory activation of EC, indicating that this process was mediated through canonical NF-κB signalling. Interestingly, inactivation of NIK also decreased LTβR-induced expression of inflammatory cytokines and leukocyte-adhesion, but silencing of NFκB2 had no apparent effect. Further analyses, including silencing and overexpression of NIK, demonstrated a clear role for NIK in activation of the canonical NF-κB pathway by amplifying IKK complex activity. RASF stimulation of EC resulted in activation of canonical and noncanonical NF-κB signalling, and increased the expression of inflammatory cytokines and adhesion molecules, which could be blocked by targeting NIK. Conclusions: These findings suggest that in addition to regulating noncanonical signalling, NIK can serve as an amplifier of canonical NF-κB signalling and associated inflammatory responses in EC, which may play a role in development and maintenance of chronic inflammation. Consequently, NIK may be an attractive therapeutic target. Disclosure of interest: P. Kucharzewska Employee of: Employed by AstraZeneca, K. Jeucken: None declared, C. Maracle: None declared, J. P. van Hamburg: None declared, H. Olsson Employee of: Employed by AstraZeneca, S. Tas: None declared